2017
DOI: 10.1186/s41065-017-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic evaluation of off-type grasses in hybrid Bermudagrass [Cynodon dactylon (L.) Pers. x C. transvaalensis Burtt-Davy] putting greens using genotyping-by-sequencing and morphological characterization

Abstract: BackgroundInterspecific hybrid bermudagrass [Cynodon dactylon (L.) Pers. x C. transvaalensis Burtt-Davy] is one of the most widely used grasses on golf courses, with cultivars derived from ‘Tifgreen’ or ‘Tifdwarf’ particularly used for putting greens. Many bermudagrass cultivars established for putting greens can be genetically unstable and lead to the occurrence of undesirable off-type grasses that vary in phenotype. The objective of this research was to genetically and phenotypically differentiate off-type g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…In this study, we used C. transvaalensis (Fig. 1a ) for whole-genome sequencing 34 . Based on Illumina data (~18.8 Gb), k -mer frequency analysis revealed that the genome size was ~454.4 Mb (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used C. transvaalensis (Fig. 1a ) for whole-genome sequencing 34 . Based on Illumina data (~18.8 Gb), k -mer frequency analysis revealed that the genome size was ~454.4 Mb (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological variation as a response to environmental changes at different geographic positions is common in C. dactylon [38,39]. A study of 260 accessions of bermudagrass germplasm indicated that there is extensive morphological variation in C. dactylon populations along longitudinal gradients, which has been found in some other studies [31,40,41]. The correlation analysis showed that the traits of width and dimeter were seldom significantly correlated with the longitude, soil nuriture or climate.…”
Section: The Relationships Between Morphological Traits and Longitudementioning
confidence: 91%
“…Golf Association, 2017). Manifestation of off‐type grasses in genetically unstable ultradwarf bermudagrasses used on putting greens (Reasor et al., 2018) may be another factor encouraging golf course superintendents to use creeping bentgrass in lieu of ultradwarf bermudagrass. Nearly 87% (213 of 243 golf courses) reported using winter protective covers to maintain ultradwarf bermudagrass putting greens, including 100% of respondents in Alabama, Arkansas, Kentucky, Louisiana, Mississippi, North Carolina, South Carolina, Tennessee, Texas, and Virginia.…”
Section: What We Foundmentioning
confidence: 99%